2013
DOI: 10.1111/dote.12053
|View full text |Cite
|
Sign up to set email alerts
|

Thoracotomy for repair of esophageal atresia: not as bad as they want you to think!

Abstract: Is it outdated now to do a thoracotomy to repair esophageal atresia (EA)? Our practices and the literature on the subject of thoracoscopic and open thoracotomy repair of EA were reviewed, seeking answers to the following questions: Is it correct to compare the new thoracoscopic approach for the repair of EA against the thoracotomy techniques of 15-30 years ago? Should post-thoracotomy scoliosis/thoracic deformity reported in up to 56% of patients be a significant current concern? Are the clips used to close th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…44 Results published by surgeons who are pioneers in minimally invasive EA/TEF repair may not be generalizable and the complication rate from centers with less experience is likely underreported in the literature. 45 Furthermore, a recent randomized controlled trial reported that thoracoscopic EA/TEF repair can be associated with worse intraoperative acidosis and hypercapnia compared with open management. 46 However, in selected patients and with experienced teams, thoracoscopic correction of EA/TEF is appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…44 Results published by surgeons who are pioneers in minimally invasive EA/TEF repair may not be generalizable and the complication rate from centers with less experience is likely underreported in the literature. 45 Furthermore, a recent randomized controlled trial reported that thoracoscopic EA/TEF repair can be associated with worse intraoperative acidosis and hypercapnia compared with open management. 46 However, in selected patients and with experienced teams, thoracoscopic correction of EA/TEF is appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Preserving the original esophagus is the most important priority and is achieved in 90% of all cases by primary anastomosis with closure of the esophago-tracheal fistula. Even if the preferred approach is through a right-sided thoracotomy [ 3 ], in the past 10 years, thoracoscopic repair has become standard in specialized centers also for the correction of congenital and acquired TEF. A recent meta-analysis has confirmed the effectiveness of this approach, which seems to have outcomes not different from those of open surgery [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…(9) While thoracoscopic repair is apparently safe and possibly advantageous in some respects when performed by a handful of experts, it should not be touted as the 'gold standard' to be utilized by all pediatric surgeons. [8] We have used minimally invasive surgical techniques for many diseases into our experience. Now, the main aim of anyone technique is a good anastomosis, survival, limited sequels and good quality of life [9].…”
Section: Discussionmentioning
confidence: 99%